“Evaluación de eficiencia energética para mejorar los indicadores de desempeño IDEn en la finca "La Cordillera" perteneciente al Cantón Mejía, Provincia de Pichincha”. - Jiménez Jiménez, Diego David (2021)
The “La Cordillera” farm had electrical installations with voltage drops, low power factor, oversized protections, conductors without connected loads, lack of lighting studies, single-line diagrams and no electrical plans. The research sought to evaluate the efficiency of the livestock industry to improve energy performance indicators. First, the most representative carrier was identified between electricity, LPG or gasoline through the Pareto diagram, followed by the behavior of electricity consumption during the period 2018 – 2020, likewise the energy audit carried out through the network analyzer, amperimetric clamp, luxmeter, highlighted the inefficient use of electrical energy as lighting. The LED lighting system based on presence sensors used 15 lamps, in order to meet the primary criteria of light quality, save 124.60 kW∙h annually, in addition to reaching VEEI values of 1.04 W/(m2∙lx), likewise; the contactor-driven fixed reactive compensation allowed increasing the PF from 0.76 to 0.976, at the same time, it decreased the loadability of the single-phase transformer by 21.66%, thus, the IDEn were improved by obtaining results of 9,470 kW∙h/yr, 0.0517 kW∙h/L, 1,815.435 kg CO2/yr. The change from residential to non-demand commercial tariff achieved the annual monetary savings of 220.44 USD. Finally, the economic analysis reflected the profitability of the project as the net present value was 51.34 USD, internal rate return of 8.38% higher than the interest rate of 7.48% and benefit/cost ratio of 1.04.